Pharmacology and Abuse of Cocaine, Amphetamines, Ecstasy and Related Designer Drugs A comprehensive review on their mode of action, treatment of abuse and intoxication - Freye, Enno.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Finally - a book that covers all aspects of the illicit use of cocaine, amphetamines, ecstasy and/or designer drugs such as GHB, written by two experts in their field. The use of these drugs remains a continuous threat in health and medical care delivery, and this book will be an essential asset to the physician who may have to face the evaluation of patients whose use of these drugs compromises an effective treatment plan for other health issues. The book has been conceived to fill the void in existing physician reference materials, and provides a comprehensive review of the theoretical knowledge and scope of pharmacotherapy in individuals who are hooked on a psychoactive substance. While detailed scientific information is obtainable in other major articles, the book's straightforward format and style, along with its illustrations, will make for easy reading as emphasis is put on information specifically related to drugs that occur most abused in today$1 (Bs society. The information provided is based on clinical practice rather than pure experimental data, which will give the physician more effective tools useful in their daily practice. Many mechanisms of action of abuse are described in detail and references are provided to direct the reader to further sources for additional information. As a special feature, the book incorporates uncluttered tables and charts, which result in immediate clarification of the mode of action on the central nervous system and the reason for misuse, thus avoiding usual long and fatiguing text in common reference books. The book aims to give the reader a clear and concise plan on what to do when being faced with an overdose situation. A well-organized Table of Contents rapidly leads the reader from general pharmacological issues to the specific overdose syndrome and its management. Additionally, significant emphasis is placed on the practical do's and don$1 (Bts for physicians, with special reference to the predictive signs of aberrant drug-related behavior and the identification of the drug diverter by using urine drug screening.s
How It All Started with Cocaine -- Production of the Coca Leaf -- Cocaine: History of Use -- Popularity of Cocaine as a Drug for Medical Treatment -- The Different Types of Alkaloids in Coca -- The Making of Cocaine in the Jungle -- Freebase Cocaine: High Bioavailability with Increase in Potency -- Pharmacology of Cocaine -- Addictive Properties of Cocaine: Mode Of Action -- Cocaine Intoxication: Strategy for Treatment -- Special Pathologies in Chronic Cocaine Use -- Summary of Advanced Treatment in Cocaine OD -- Chronic Toxicity of Cocaine use -- Summary of Acute-Chronic Effects of Cocaine -- Cocaine Use in Pregnancy -- Methamphetamine-an Old Aquaintance in New Clothes -- New Options in the Treatment of Cocaine Dependency -- Mode of Action of Methamphetamine -- Pharmacology of Methamphetamine -- Crystal Methamphetamine -- Treatment Options in Methamphetamine Addiction and Withdrawal -- Amphetamine Derivatives as Appetite Suppressants -- Incidence of Illicit Use of Ecstasy -- Pharmacology of Ecstasy (MDMA) -- Pharmacological Effects of MDMA in Man -- Pharmacokinetics of MDMA -- MDMA (Ecstasy): from Psychotherapy to a Street Drug of Abuse -- History of Designer Drugs -- Gamma-Hydroxybutyric (GHB) Acid -- The Pharmacology of ?-Hydroxybutyric Acid (GHB) -- Use of GHB in Clinical Medicine -- Abuse Potential and Intoxication with GHB -- Benzylpiperazine (BZP) as a Designer Drug -- Natural Products with Abuse Potential -- Toxicity of Datura Stramonium -- Dimethyltryptamine (DMT) a Psychedelic -- The Mushroom Psilocybin with Psychedelic Properties -- Ibogaine, Psychedelic Molecule with Anti-Addictive Properties -- Peyote, a Mescaline-Containing Cactus -- LSD, a Semisynthetic Psychedelic Drug -- 5-MeO-DIPT, a Psychedelic Structurally Related to Psiloc(yb)in -- Positive Signs and Symptoms of Hard Drug Abuse -- Urine Drug Screening (UDS): Identifying the Person with Illicit Use -- Types of Urine Drug Testing -- Designer Drugs and their Abuse -- Type of Tests for Urine Drug Testing (UDT) -- How to Demask the Patient with an Aberrant Drug Use -- Analysis of Saliva, Hair and Sweat for Drug Testing.
Keywords: Medicine; Toxicology; Pharmaceutical technology; Pharmacy; Emergency medicine; Biomedicine; Pharmacology/Toxicology.; Pharmaceutical Sciences/Technology.; Pharmacy; Medicine/Public Health, general; Emergency Medicine; Biomedicine general